2015
DOI: 10.1039/c4mb00689e
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations in inter-domain associations may trigger the onset of pathogenic transformations in PrPC: insights from atomistic simulations

Abstract: Conversion of the predominantly α-helical cellular prion protein (PrP(C)) to the misfolded β-sheet enriched Scrapie form (PrP(Sc)) is a critical event in prion pathogenesis. However, the conformational triggers that lead to the isoform conversion (PrP(C) to PrP(Sc)) remain obscure, and conjectures about the role of unusually hydrophilic, short helix H1 of the C-terminal globular domain in the transition are varied. Helix H1 is anchored to helix H3 via a few stabilizing polar interactions. We have employed full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 86 publications
(225 reference statements)
2
12
0
Order By: Relevance
“…As expected, the benchmark simulation of the inactive compound BMD01 displayed a similar helical loss compared to free PrP C and the active compound GN8 retained the helical content (Figure S2D). As in earlier simulation studies, the end of the α1 region, which consists of residues 154–156, formed continued 3 10 ‐helix in antiprion compound‐stabilized PrP C , while in the absence of an antiprion compound, these residues mostly adopted a helical conformation …”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…As expected, the benchmark simulation of the inactive compound BMD01 displayed a similar helical loss compared to free PrP C and the active compound GN8 retained the helical content (Figure S2D). As in earlier simulation studies, the end of the α1 region, which consists of residues 154–156, formed continued 3 10 ‐helix in antiprion compound‐stabilized PrP C , while in the absence of an antiprion compound, these residues mostly adopted a helical conformation …”
Section: Resultssupporting
confidence: 66%
“…However, these regions are unstable in PrP C and experience large conformational changes in the absence of antiprion compounds, as demonstrated in a previous study . Although it is well established that hydrophobic core interactions in PrP C are the driving force in prion folding, we observed that these interactions are conserved in the presence of antiprion compounds. Therefore, we performed a simulation of PrP C with the well‐determined antiprion compound, GN8, to evaluate the accuracy of our procedure; the results were similar to those obtained using our discovered antiprion compounds.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…Salt‐bridge ionic interactions are important for protein stability, conformational specificity, and for positioning key residues that are essential for protein folding and function . Salt‐bridge interactions can provide the structural specificity required for proper folding of individual domains as well as guiding domain–domain association.…”
Section: Introductionmentioning
confidence: 99%